Controlling guest conformation for efficient purification of butadiene - Liao, Pei-Qin; Huang, Ning-Yu; Zhang, Wei-Xiong; Zhang, Jie-Peng; Chen, Xiao-Ming (Science (American Association for the Advancement of Science), 2017)
Conventional adsorbents preferentially adsorb the small, high-polarity, and unsaturated 1,3-butadiene molecule over the other C₄ hydrocarbons from which it must be separated. We show from single-crystal x-ray diffraction and computational simulation that a hydrophilic metal-organic framework, [Zn₂(btm)₂], where H₂btm is bis(5-methyl-1H-1,2,4-triazol-3-yl)methane, has quasi-discrete pores that can induce conformational changes in the flexible guest molecules, weakening 1,3-butadiene adsorption through a large bending energy penalty. In a breakthrough operation at ambient temperature and pressure, this guest conformation–controlling adsorbent eluted 1,3-butadiene first, then butane, butene, and isobutene. Thus, 1,3-butadiene can be efficiently purified (≥99.5%) while avoiding high-temperature conditions that can lead to its undesirable polymerization.